A new species of Caligus Müller, 1785 (Copepoda: Siphonostomatoida: Caligidae) from coral reef plankton in the Mexican Caribbean - Suárez-Morales, Eduardo; Gasca, Rebeca (Zootaxa, 2016)
During a survey of the zooplankton community of a protected reef system on the southern coast of the Mexican Caribbean, many female and male specimens of an undescribed species of Caligus Müller, 1785 were collected. The new species closely resembles C. wilsoni Delamare Deboutteville & Nunez-Ruivo, 1958 and C. belones (Krøyer, 1863) and has affinities with C. balistae Steenstrup & Lütken, 1861 and C. longipedis Bassett-Smith, 1898, all known from the Caribbean Sea and adjacent waters of the north-western Atlantic Ocean. Caligus ilhoikimi sp. nov., is described in full and illustrations of both sexes are also provided. The new species differs from C. wilsoni and C. belones in several features, including the shape of the sternal furca, the shape and proportions of the genital complex and abdomen, the lack of accessory processes on the distal elements of leg 1 exopod, and the presence of a lateral spine on the third exopodal segment of leg 2. This is the seventh species of Caligus known from waters of the Atlantic seaboard of Mexico and the 32nd species of the genus recorded in Mexican waters. The specimens were caught with a plankton light trap. The unusually high number of individuals captured and the fact that the sample was monospecific (i.e. only adults of this caligid species were collected) suggests that it is a chiefly planktonic form. This is a mode of life recently revealed as being more common among caligids than previously thought.